Critical perspectives on Esports - Hofmann, Annette R. 1966-; Mamudou Camara, Pascal (ICSSPE perspectives, 2024)
"This book offers new, multi-disciplinary perspectives on esports, one of the most rapidly growing sectors in the sport and leisure industries. Drawing on sociology, philosophy, education, business, economics and sport science, the book considers the rise of esports, its impact on sport and society more widely, and the direction of travel for esports in the future. Featuring cutting-edge work from researchers in Europe, North America and Asia, the book explores definitions of 'esport' and 'virtual sport', and the philosophical basis by which we understand movement and embodiment in the context of digital gaming. It considers the health and wellbeing needs of esports athletes, across physical, mental and social dimensions, as well as how nutrition and training relate to performance and injury prevention. The book goes on to consider the economics of the esport industry, and how the concept of sportification can be used to describe esports' development, as well as the challenges and debates surrounding gender and representation in esports. A final section of the book looks at esports in education, in schools and universities, and considers the future of esports for a generation of digital natives. This book makes a useful contribution to the growing body of knowledge on esports and should be a thought-provoking read for anybody with an interest in sport studies, gaming, or the impact of technology on wider society"--